Bovine viral diarrhoea virus (BVDV) does not use macropinocytosis or claveolae-mediated endocytic pathway for entry into bovine or ovine cells while brefeldin A inhibits its release in ovine cells - DUBEY, POOJA; MISHRA, NIRANJAN; BEHERA, S P; PRAKASH, ANIL (The Indian Journal of Animal Sciences, 2015)
Present knowledge on bovine viral diarrhoea virus (BVDV) entry, morphogenesis and release in host cells is incomplete. This study reports the results of effect of drug cytochalasin D and nystatin on BVDV entry in bovine and ovine cells and effect of Brefeldin-A (BFA), on BVDV release in ovine cells. The bovine (MDBK) and ovine (SFT-R) cells were treated with various concentrations of cytochalasin D or nystatin before infection with BVDV and at 16 h post infection, the number of infected cells was determined by immunochemistry. The ovine cells were infected with BVDV before addition of different concentration of BFA at 8 h post infection and the supernatants at 24 hpi were subjected to RT-PCR or immunochemistry. The results showed that only a minor inhibitory effect was observed on the entry and infectivity of BVDV in both ovine and bovine cells even at highest concentration of cytochalasin D or nystatin. As revealed by RT-PCR and virus titration, BFA treatment inhibited the BVDV secretion in a dose-dependent manner with complete inhibition obtained by 2μg/ml of BFA. However, the intracellular virus particles in BFA treated cell pellet were infectious. Taken together, our results showed that entry of BVDV into bovine or ovine cells is not dependent on macropinocytosis or claveolae-mediated endocytosis and provided evidence of existence of a common mechanism of BVDV release in bovine and ovine cells.